Genetic and molecular analysis of new female-specific lethal mutations at the gene Sxl of Drosophila melanogaster. - Granadino, B.; Torres, M.; Bachiller, D.; Torroja, E.; Barbero, J.L.; Sanchez, L. (Genetics, 1991)
We have isolated three female-specific lethal mutations at the gene Sex-lethal (Sxl): Sxlfb, Sxlfc and Sxlfd. We have carried out the complementation analysis between these mutations and other previously reported Sxlf mutations. It is possible to classify the alleles tested in this report into two complementation groups: the bc group defined by Sxlfb, and Sxlfc, and the LS group defined by SxlfLS. The other alleles tested affect both complementation groups albeit with different degrees. Contrary to what happens with mutations at the LS group, mutations at the bc group do not affect sex determination, nor late dosage compensation nor oogenesis. Both Sxlfb and Sxlfc present a DNA insertion of at least 5 kb between position -10 and -11 on the molecular map, within the fourth intron. On the contrary, Sxlfd, a strong mutation affecting all Sxl functions, is not associated to any detectable DNA alteration in Southern blots, so that it seems to be a "point" mutation. In agreement with their phenotypes, both Sxlfc/SxlfLS and Sxlfc homozygous female larvae express only the late Sxl transcripts characteristic of females, while females homozygous for SxlfLS express only the late Sxl transcripts characteristic of males. Moreover, Sxlfc presents a lethal synergistic interaction with mutations at either da or the X:A ratio, two signals that define the initial activity state of Sxl, while SxlfLS do not. These data suggest that the two complementation groups are related to the two sets of early and late Sxl transcripts, which are responsible for the early and late Sxl functions, respectively: Sxlfb and Sxlfc would affect the early functions and SxlfLS would affect the late Sxl functions.